Going viral: A science communication collaboration in the era of COVID-19 and social media - Wiles, Siouxsie; Morris, Toby; Priestley, Rebecca (Frontiers in Communication, 2023)
On 9 March 2020, two days before the World Health Organization declared COVID-19 a global pandemic, microbiologist and infectious diseases expert Associate Professor Siouxsie Wiles released the first output from her collaboration with cartoonist Toby Morris: an animated GIF (Graphics Interchange Format) known as ‘Flatten the Curve’. The graphic went viral on Twitter with over 10 million impressions in three days. Flatten the Curve was the first of more than 70 graphics produced by the Wiles and Morris collaboration, all designed as accessible visual communication about COVID-19. The graphics, all released under a Creative Commons CC-BY-SA-4.0 license, have been translated into multiple languages, used by communities, politicians, and public health officials around the world, and the collaborators have won multiple awards for their work.